PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT PERMODALAN NASIONAL MADANI AREA BOGOR 4 - Nengsih Nawangsih; Kenny Astria (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the effect of Leadership Style and Work Motivation on Employee Performance at PT Permodalan Nasional Madani, Area Bogor 4. The research method employed is quantitative, with a sampling technique using Slovin’s formula, involving 60 respondents. The results of the study indicate that Leadership Style does not have a significant effect on Employee Performance, with the regression equation Y = 20.174 + 05.523X1 and a correlation coefficient of 0.705, indicating a strong relationship between the two variables, though the determination value is only 0.085 or 8.5%. The hypothesis test yielded a t-value of t count < t table (0.530 < 1.672), meaning H0 is accepted and Ha is rejected, suggesting no significant effect of Leadership Style on Employee Performance. Work Motivation has a significant effect on Employee Performance, with the regression equation Y = 11.349 + 0.671X2, a correlation coefficient of 0.871, showing a strong relationship, and a determination value of 0.544 or 54.4%. The hypothesis test showed t count > t table (5.424 > 1.672), meaning H0 is rejected and Ha is accepted, indicating a significant effect of Work Motivation on Employee Performance. Simultaneously, Leadership Style and Work Motivation have a significant effect on Employee Performance, with the regression equation Y = 11.349 + 0.055X1 + 0.671X2. The correlation coefficient was found to be 0.818, indicating a strong relationship between the variables, with a determination value of 0.5310 or 53.1%. The hypothesis test showed F count > F table (57.515 > 3.159), meaning H0 is rejected and Ha is accepted. This indicates that there is a significant simultaneous effect of Leadership Style and Work Motivation on Employee Performance at PT Permodalan Nasional Madani, Area Bogor 4.